2015
DOI: 10.1111/eth.12402
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Affinities Play a Key Role in the Organisation of Collective Movements in a Group of Domestic Horses

Abstract: Understanding how groups of individuals with different motives come to daily decisions about the exploitation of their environment is a key question in animal behaviour. While interindividual differences are often seen only as a threat to group cohesion, growing evidence shows that they may to some extent facilitate effective collective action. Recent studies suggest that personality differences influence how individuals are attracted to conspecifics and affect their behaviour as an initiator or a follower. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 93 publications
(187 reference statements)
1
63
4
1
Order By: Relevance
“…Though previous research has shown that certain keystone individuals can have a disproportionate effect on group dynamics (reviewed in: Modlmeier et al, ), either because they are more informed (e.g., Dyer et al, ) or have a certain personality or temperament (e.g., Briard, Dorn, & Petit, ; Harcourt et al, ; Kurvers et al, ), our analysis did not demonstrate that a single individual in our vervet group could be considered vital to the success or failure of a group progression. To qualify as a “key” individual in our study, he or she had to have been involved in few unsuccessful progressions and have a large number of followers within a short amount of time after joining a progression.…”
Section: Discussioncontrasting
confidence: 63%
“…Though previous research has shown that certain keystone individuals can have a disproportionate effect on group dynamics (reviewed in: Modlmeier et al, ), either because they are more informed (e.g., Dyer et al, ) or have a certain personality or temperament (e.g., Briard, Dorn, & Petit, ; Harcourt et al, ; Kurvers et al, ), our analysis did not demonstrate that a single individual in our vervet group could be considered vital to the success or failure of a group progression. To qualify as a “key” individual in our study, he or she had to have been involved in few unsuccessful progressions and have a large number of followers within a short amount of time after joining a progression.…”
Section: Discussioncontrasting
confidence: 63%
“…Using spatial-positioning data, Bourjade et al (2015) and Briard et al (2015) reported that there might be no leaders on collective departure in domestic horses and the influence of a stallion on the group behavior is not strong (Bourjade et al 2015;Briard et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it seems that the organisation of the zebrafish groups (2 nd , 3 rd and last ranked fish) during the collective departures is topological. Other studies about the organisations of collective departures show a joining process for Equus ferus caballus that is related to affinities and hierarchical rank [59]. Rosenthal et al show that, in groups of Notemigonus crysoleucas, the initiator is the closest fish from the group boundary in 27% of the cases and the first responder is the closest fish from the group boundary in 19% of the cases [30].…”
Section: Discussionmentioning
confidence: 99%
“…For bigger groups, these distributions are significantly different from a random uniform distribution which means that there are preferential interactions. Preferential interactions have been evidenced in other species: Briard et al [59] show affinities, hierarchy and pairs interactions in a group of domestic horses, [60][61][62][63] show that the affinity between individuals (monkeys, Macaca mulatta, Macaca tonkeana, Papio ursinus; or fish, Gasterosteus aculeatus) play a role in the collective movements. We propose two hypotheses that could explain the change of the interactions between pairs of zebrafish when changing the number of individuals.…”
Section: Discussionmentioning
confidence: 99%